Capillary Electrophoresis Separations of Glycans - Lu, Grace (Chem Rev, 2018)
[Image: see text] Capillary electrophoresis has emerged as a powerful approach for carbohydrate analyses since 2014. The method provides high resolution capable of separating carbohydrates by charge-to-size ratio. Principle applications are heavily focused on N-glycans, which are highly relevant to biological therapeutics and biomarker research. Advances in techniques used for N-glycan structural identification include migration time indexing and exoglycosidase and lectin profiling, as well as mass spectrometry. Capillary electrophoresis methods have been developed that are capable of separating glycans with the same monosaccharide sequence but different positional isomers, as well as determining whether monosaccharides composing a glycan are alpha or beta linked. Significant applications of capillary electrophoresis to the analyses of N-glycans in biomarker discovery and biological therapeutics are emphasized with a brief discussion included on carbohydrate analyses of glycosaminoglycans and mono-, di-, and oligosaccharides relevant to food and plant products. Innovative, emerging techniques in the field are highlighted and the future direction of the technology is projected based on the significant contributions of capillary electrophoresis to glycoscience from 2014 to the present as discussed in this review.